FORMULASI DAN UJI MUTU FISIK SEDIAAN PERMEN JELLY FRAKSI ETIL ASETAT BUAH KEMUKUS (Piper cubeba L.f) - Amanda Risky Damayanti; Gigih Kenanga Sari; Wahyu Purwanjani (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
The ethyl acetate fraction of cubeb fruit (Piper cubeba L.f) contains alkaloid, flavonoid and terpenoid compounds that function to improve memory. Jelly candy is currently popular and is one of the favorite foods in various circles, because it has a chewy characteristic, therefore a new innovation was made in developing cubeb fruit. This study aims to determine the physical quality of the ethyl acetate fraction of cubeb fruit jelly candy preparation. The physical quality test consists of organoleptic color, scent and texture, water content, ash content, reducing sugar, pH, and weight uniformity. The formulation of the jelly candy preparation uses ethyl acetate fraction and is divided into 3 formulations with the concentrations used, namely 0.488g, 0.977g, 1.955g. The results of physical quality tests of FI, FII and FIII jelly candy preparations meet the requirements according to SNI standards including: organoleptic tests of color, aroma and texture, water content, ash content, reducing sugar, pH, and weight uniformity. The ethyl acetate fraction of cubeb fruit has alkaloid, flavonoid, and terpenoid compounds. The ethyl acetate fraction of cubeb fruit can be formulated into jelly candy preparations, all formulations have good physical quality according to SNI standards and formulation I is the best formulation.